The Main Problems of Ensuring the Implementation of the Uniform State Policy Directed to the Wise Use of Earth Resources and Their Protection (Zien Journal of Social Sciences and Humanities, 2022)
In this article, we introduce a procedure for allocating land plots that is equal for all, transparent and based on market principles, ensuring stability in property and legal relations related to land, protecting land, guaranteeing the property rights of land owners, as well as establishing its civil legal relations by determining the economic value of land. issues related to the regulation of limited use of land plots, implementation of servitude rights and regulation of land relations, scientific-practical and theoretical problems of regulation of the right to limited use of land plots and areas of use are covered in detail.